POLITIK PERBEDAAN: MINORITAS DALAM IMPLEMENTASI KEBIJAKAN - M. Dian Hikmawan (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
Abstract Public policy is always closely connected with the articulation of a distribution and re-distribution. Wisest form of policy that can accommodate all people without exception. Therefore, in the implementation of the public policy, it’s important to view the differences of social group not as a threat. but recognizing them through the political differences. Imbalances in the system which is too liberal governance is always to make people as several individuals with their rights. Finally, the policy only view the majority as a strong power which able to exclude those who are weak and considered different from the majority rule. This article at least invites us to re-articulate what is to be achieved in a democracy by analyzing the implementation of policy for difference groups are excluded by majority rule. Keywords: politics of difference, minority, majority, public policy